Pengaruh Penggunaan Buku Siswa IPA Terpadu Model Networked dengan Tema Kelistrikan Jantung Terhadap Penguasaan Materi IPA Peserta Didik Kelas VIII MTsN 6 Model Padang - Silvia Agustin; Ratnawulan Ratnawulan; Gusnedi Gusnedi (PILLAR OF PHYSICS EDUCATION, 2018)
Based on the curriculum of 2013 science learning at school is implemented in an integrated manner using a scientific approach or scientific process-based approach. Integrated science learning connects physical, chemical and biological material because these three materials cannot be separated. The reality at schools shows that integrated science learning is still carried out separately and lack of student understanding in integrating science materials. The solution to this problem is to apply the Integrated Science Student Model Book Networked with the Heart Electricity Theme. This resesarch aims to investigate the influence of integrated science book modeled network students with the theme of heart electricity to the mastery of science material for students at class VIII MTsN 6 model Padang. The type of research conducted is a quasi-experimental research design with One Group Pretest-Posttest Design research. The population in this research were all students at class VIII MTsN 6 model Padang registered in the 2017/2018 academic year. Sampling in the research was carried out with purposive sampling and cluster random sampling techniques. The sample in this resesarch is class VIII.1 as an experimental class of 36 peoples. The research instrument consists of a test sheet of learning outcomes to assess aspects of knowledge, a performance assessment sheet to assess aspects of student skills and students' self-evaluation sheets. The data in this research were analyzed using descriptive analysis, simple linear regression, and product moment correlation test at a significance level of 0.05 for both aspects of competence. Based on the results of the research that has been done, it is obtained data for aspects of knowledge, and skills. The results of data analysis showed that the average post-test value was higher than the average value of the pre-test, namely 81.39> 49.03. In knowledge competence the coefficient of determination is 13.64%. In the skill competence, the determination coefficient value is 13.63%. Quantitatively, the working hypothesis that reads "There is an influence which means the use of integrated science students' book networked model with the the heart electricity theme to the science material mastery of students at class VIII MTsN 6 Model Padang" can be accepted at a significant level of 0.05. Mastery of students' science materials can also be seen from the results of the self-evaluation sheet filled by students who stated that they understood more than 65% of the material they had learned. Thus, the use of integrated science students 'book networked model with the heart electricity theme influences the student mastery material on aspects of knowledge and skills.